RP1 Dominant p.Ser740* Pathogenic Variant in 20 Knowingly Unrelated Families Affected by Rod–Cone Dystrophy: Potential Founder Effect in Western Sicily - Fabiana D’Esposito; Viviana Randazzo; Maria Igea Vega; Gabriella Esposito; Paolo Enrico Maltese; Salvatore Torregrossa; Paola Scibetta; Florinda Listì; Caterina Gagliano; Lucia Scalia; Antonino Pioppo; Antonio Marino; et al. (Medicina, 2024)
Background and Objectives. Retinitis pigmentosa (RP) is the most common inherited rod–cone dystrophy (RCD), resulting in nyctalopia, progressive visual field, and visual acuity decay in the late stages. The autosomal dominant form (ADRP) accounts for about 20% of RPs. Among the over 30 genes found to date related to ADRP, RP1 pathogenic variants have been identified in 5–10% of cases. In a cohort of RCD patients from the Palermo province on the island of Sicily, we identified a prevalent nonsense variant in RP1, which was associated with ADRP. The objective of our study was to analyse the clinical and molecular data of this patient cohort and to evaluate the potential presence of a founder effect. Materials and Methods. From 2005 to January 2023, 84 probands originating from Western Sicily (Italy) with a diagnosis of RCD or RP and their relatives underwent deep phenotyping, which was performed in various Italian clinical institutions. Molecular characterisation of patients and familial segregation of pathogenic variants were carried out in different laboratories using Sanger and/or next-generation sequencing (NGS). Results. Among 84 probands with RCD/RP, we found 28 heterozygotes for the RP1 variant c.2219C>G, p.Ser740* ((NM_006269.2)*, which was therefore significantly prevalent in this patient cohort. After a careful interview process, we ascertained that some of these patients shared the same pedigree. Therefore, we were ultimately able to define 20 independent family groups with no traceable consanguinity. Lastly, analysis of clinical data showed, in our patients, that the p.Ser740* nonsense variant was often associated with a late-onset and relatively mild phenotype. Conclusions. The high prevalence of the p.Ser740* variant in ADRP patients from Western Sicily suggests the presence of a founder effect, which has useful implications for the molecular diagnosis of RCD in patients coming from this Italian region. This variant can be primarily searched for in RP-affected subjects displaying compatible modes of transmission and phenotypes, with an advantage in terms of the required costs and time for analysis. Moreover, given its high prevalence, the RP1 p.Ser740* variant could represent a potential candidate for the development of therapeutic strategies based on gene editing or translational read-through therapy for suppression of nonsense variants.